A retrospective comparison of endoscopic stenting alone with stenting and radiotherapy in non-resectable cholangiocarcinoma. Issue 6 (December 1996) - Bowling, T E; Galbraith, S M; Hatfield, A R; Solano, J; Spittle, M F
Abstract : BACKGROUND AND AIMS: Radiotherapy has been reported to be of benefit in prolonging the survival of patients with cholangiocarcinoma. This study examined whether radiotherapy in addition to endoscopic stenting improved survival. SUBJECTS: 56 patients with obstructive jaundice due to histologically confirmed non-resectable cholangiocarcinoma. METHODS: A retrospective analysis of these patients who were treated either with endoscopic biliary stenting followed by external beam radiotherapy and internal iridium-192 brachytherapy (n = 28) or with stenting alone (control group; n = 28). RESULTS: The two groups were well matched in age, sex, and stricture type. Eighteen patients had a type I stricture (control group: 11; radiotherapy group: 7) at the time of diagnosis and 38 had a type II or III stricture (control group: 17; radiotherapy group: 21). The median (range) overall survival from diagnosis was seven (1-29) and 10 (4-75) months in the control and radiotherapy groups respectively: This difference did not reach statistical significance (p = 0.06), but survival plots indicated a survival advantage in the radiotherapy group in the first nine months after diagnosis. Approximately one third survived longer than one year in both groups. More patients in the radiotherapy group required a stent change (1.9 v 0.9: p = 0.05), and also had a longer overall inpatient stay (42 days v 19: p < 0.001). When examined on the basis of stricture type, there was a survival advantage in the first 10 months after diagnosis in those with a type II/III stricture (seven and 11 months in the radiotherapy and control groups respectively: 0.01 < p < 0.05). There was no difference in survival between the groups in those with a type I stricture. Numbers surviving longer than one year, stent survival, and number of stent changes were all similar between the two groups when examined on the basis of stricture type, but length of hospital stay remained considerably longer in all patients receiving radiotherapy. CONCLUSION: The survival advantage of radiotherapy in those with a type II/III stricture is seen only in the first 10 months after diagnosis. The costs of radiotherapy and significantly increased time spent in hospital, however, raise doubts over its routine use in the management of non-resectable cholangiocarcinoma.